2007
DOI: 10.4314/thrb.v9i2.14312
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality assurance in HIV testing in health facilities in Lake Victoria zone, Tanzania

Abstract: Tanzania is currently implementing the antiretroviral treatment programme, and has a target of putting about 400,000 eligible HIV infected individuals on treatment by 2008. This will involve screening a large number of people, which will require non-laboratory personnel to be involved in doing HIV testing. In order to guarantee reliable and quality HIV test results, there is a need to ensure that quality assurance (QA) procedures are followed from specimen collection, testing and reporting of results. In light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 2 publications
2
22
0
Order By: Relevance
“…Yet despite donor support, HIV has put health care delivery under significant strain which has affected the relationship between client and health worker. Several studies have highlighted problems like lack of skills and shortage of drugs as obstacles in scaling up HIV treatment [30,31]. Building on similar findings, this study has shown how problems like the shortage of drugs, long waiting times, short consultation times and poor service affect the health worker-client relationship.…”
Section: Discussionsupporting
confidence: 65%
“…Yet despite donor support, HIV has put health care delivery under significant strain which has affected the relationship between client and health worker. Several studies have highlighted problems like lack of skills and shortage of drugs as obstacles in scaling up HIV treatment [30,31]. Building on similar findings, this study has shown how problems like the shortage of drugs, long waiting times, short consultation times and poor service affect the health worker-client relationship.…”
Section: Discussionsupporting
confidence: 65%
“…However, as observed before by other qualitative studies in the region [7] [8], the present study identified a number of gaps when compared with the WHO minimum standard guidelines in provision of VCT and ART services. The results from our study do confirm that these inadequacies affected the effective operations of the facility.…”
Section: Discussionsupporting
confidence: 67%
“…Studies conducted in different regions after the roll out of care and treatment plan for HIV/AIDS in Tanzania, showed that most of the laboratories were not properly adhering to good laboratory practice (GLP), with poor laboratory quality control for HIV testing reagents, and were not performing internal and external quality control [22, 23]. Other studies conducted in similar settings also showed that health personnel were dissatisfied with HIV diagnostic services provided by their laboratories with higher dissatisfaction rates in public health facilities than in the private sector [24].…”
Section: Introductionmentioning
confidence: 99%